2018
DOI: 10.1016/j.lungcan.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II study of fulvestrant and erlotinib compared with erlotinib alone in patients with advanced or metastatic non-small cell lung cancer

Abstract: Addition of fulvestrant to erlotinib was well tolerated, with increased activity noted among EGFR wild type patients compared to erlotinib alone, albeit in an unplanned subset analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
0
37
0
1
Order By: Relevance
“…Several clinical trials have evaluated fulvestrant treatment in combination with EGFR TKIs in NSCLC based on the preclinical discovery of crosstalk between these two pathways. These combination treatments were shown to be well-tolerated by NSCLC patients and demonstrated a moderate increase in responsiveness and OS compared to the single treatment arm alone (90,91). A component of the Phase I study of gefitinib combined with fulvestrant evaluated the correlative relationship between tumoral ERα and ERβ protein expression and response to treatment.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Several clinical trials have evaluated fulvestrant treatment in combination with EGFR TKIs in NSCLC based on the preclinical discovery of crosstalk between these two pathways. These combination treatments were shown to be well-tolerated by NSCLC patients and demonstrated a moderate increase in responsiveness and OS compared to the single treatment arm alone (90,91). A component of the Phase I study of gefitinib combined with fulvestrant evaluated the correlative relationship between tumoral ERα and ERβ protein expression and response to treatment.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…An improvement in median overall survival was seen among all patients who received the dual therapy. 26 The improvement when combining erlotinib (which only targets EGFR) with fulvestrant was modest, and our results here indicate that clinical effects might be further improved if HER2/HER3 signaling was also suppressed. Our preclinical evidence shows synergy using the combination of the antiestrogen fulvestrant with dacomitinib, a pan-HER TKI recently FDA approved in EGFRmutant lung cancer.…”
Section: Discussionmentioning
confidence: 62%
“…EGFR‐TKIs show a clinical benefit for patients with NSCLC harbouring EGFR‐activating mutations; however, NSCLC with wild‐type EGFR unfortunately has a minimal activity to EGFR‐TKIs and chemotherapy remains an important component of treatment . Meanwhile, the majority of patients with NSCLC worldwide are EGFR wild‐type; thus, novel therapeutic strategies are urgently required for treating EGFR wild‐type NSCLC patients . The combination of EGFR‐TKI with other agent is effective to treat EGFR wild‐type NSCLC patients .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Meanwhile, the majority of patients with NSCLC worldwide are EGFR wild-type; thus, novel therapeutic strategies are urgently required for treating EGFR wild-type NSCLC patients. 35 The combination of EGFR-TKI with other agent is effective to treat EGFR wild-type NSCLC patients. 36,37 In our study, DYRK1A inhibitor harmine plus AZD9291 showed synergistic anti-cancer activity in EGFR wild-type NSCLC cell lines, including A549, NCI-H1299 and NCI-H460 cells.…”
Section: Egfr-tkis Show a Clinical Benefit For Patients With Nsclc Har-mentioning
confidence: 99%